2011
DOI: 10.1021/ef200282q
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Methane Displacement Behavior by Cyclic, Pure Carbon Dioxide Injection in Dry, Powdered, Bituminous Indian Coals

Abstract: Understanding competitive sorption effects for the carbon dioxideÀmethane system in coal is essential for the implementation of enhanced methane production with concomitant CO 2 sequestration in coal. The paper discusses the methane displacement behavior of a set of eight dry, powdered Indian bituminous coal samples when subjected to cyclic, pure CO 2 injection, employing a "huff and puff" scheme. The coal samples were partially saturated with methane, and CO 2 was then injected at a fixed pressure. This was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 37 publications
6
18
0
Order By: Relevance
“…Horizontal drilling and high‐volume hydraulic fracturing are common techniques in shale gas extraction, however, the accompanying threats to the environment and human health are of concern, which is the bottleneck in the development . Recently, a notable technique that uses nonaqueous fracturing fluids of supercritical CO 2 to enhance the recovery of natural gas (CO 2 ‐EGR) has been recognized as a remarkable technique that could not only conquer the energy source exploitation problems but also achieve the capture and sequestration of CO 2 to thereby combine environmental and industrial benefits perfectly …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal drilling and high‐volume hydraulic fracturing are common techniques in shale gas extraction, however, the accompanying threats to the environment and human health are of concern, which is the bottleneck in the development . Recently, a notable technique that uses nonaqueous fracturing fluids of supercritical CO 2 to enhance the recovery of natural gas (CO 2 ‐EGR) has been recognized as a remarkable technique that could not only conquer the energy source exploitation problems but also achieve the capture and sequestration of CO 2 to thereby combine environmental and industrial benefits perfectly …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Recently,an otable techniquet hat uses nonaqueous fracturing fluidso fs upercritical CO 2 to enhance the recovery of natural gas (CO 2 -EGR) has been recognized as ar emarkablet echnique that could not only conquer the energy source exploitationp roblems but also achieve the capturea nd sequestrationo fC O 2 to thereby combine environmentala nd industrial benefitsperfectly. [16][17][18][19][20] Thev ast majority of the shale gas reserved in shale formations is in an adsorbed state in nanoscale pores,w hich includes micropores( diameter (d) < 2nm) and mesopores (d = 2-50 nm). [11,21,22] Therefore, as tudy on the microbehavior of shale gasi nn anopores with ap ore size that changes from micro-to mesopores ize is meaningful to determine the mechanisms and evaluate the potential of the recoveryo f shale gas.…”
mentioning
confidence: 99%
“…Due to its sorption and structural properties, coal is a rock which is probably the most promising reservoir rock for CO 2 storage [14]. Laboratory studies of CO 2 /CH 4 exchange sorption in the context of assessing the possibility of underground storage of CO 2 in coal seams are carried out on a large scale [15][16][17][18][19][20][21][22][23][24][25]. There have also been many ECBM (Enhanced Coalbed Methane recovery) pilot/demonstration test projects in the world (e.g., in USA, Canada, China, Japan and Poland), by injecting CO 2 into coal seams [26].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al 24 built an experimental apparatus to obtain the transport characteristics of methane in nanopores and found that carbon dioxide is easier to be adsorbed by the pore surface than methane. Bhowmik et al 25 investigated the displacement behavior of methane by pure carbon dioxide in dry, powdered, bituminous Indian coals. It was also found that carbon dioxide is preferentially adsorbed by silt pores compared with methane.…”
Section: Introductionmentioning
confidence: 99%